Value Co-Creation in Corporate Esports Leagues Players' Experiences - Karnasaari, Elmeri (2024)
This master’s thesis studies the experiences of corporate esports league players and explores the impact on perceived value co-creation in these experiences. The study aims to understand what the experiences are like for Finnish corpo-rate esports league Kanaliiga’s players and how these experiences impact the perceived value co-creation in the process. The theoretical foundation of ser-vice-dominant logic and value co-creation shows that the players are actors in value co-creation process and the 2010 framework of value co-creation in con-sumer information systems by Tuunanen, Cassab and Mayers provides a lens for understanding how the system value propositions, and customer value drivers can be viewed from the players experiences. The empirical part of the study employs a qualitative approach by eight semi-structured interviews and a thematic analysis of the interview transcripts. Adaptation of the Tuunanen, Cassab and Mayers 2010 framework is then used to review the emerged themes from the data to understand how the players experiences impact the perceived value co-creation. This study contributes to the esports literature by exploring an unstudied aspect of it, that is corporate esports leagues, and by providing more insight into the value co-creation in esports. The study recognizes seven themes from the players’ experiences: unawareness of the employers, employ-ee orientation, hobbyism, having fun, competitiveness, communality and ease of use. Furthermore, the study shows that these emerged themes impact the perceived value co-creation positively and that the general user experiences of the players are positive.